Characterization and phylogenetic analysis of the mitochondrial genome of Hemitripterus villosus. Issue 2 (2nd April 2020) - Wang, Maolin; Liu, Gang; Wang, Zhengang; Wang, Wei; Li, Xuejie
Abstract: Hemitripterus villosus is an important economic fish. With the completion of H. villosus mitochondrial genome sequencing, the full-length mitochondrial genome of H. villosus was assembled and analyzed. All results indicate that the complete mitochondrial genome of H. villosus was 17, 228 bp. There were 22 tRNAs and 13 protein-coding genes (PCGs), and 2 rRNA. Besides, the phylogenetic tree of 19 teleost fish was constructed. The results showed that H. villosus was clustered with other sculpins, which including Cottus reinii, C. czerskii and Hexagrammos otakii . This mitogenome will contribute to the further systematics and evolution study of H. villosus.